Graphene oxide based heterojunction TiO2-ZnO catalysts with outstanding photocatalytic performance for bisphenol-A, ibuprofen and flurbiprofen - Simsek, Esra Bilgin; Kilic, Bayram; Asgin, Mansur; Akan, Ayse (ELSEVIER SCIENCE INC, 2018)
Reduced graphene oxide based TiO2-ZnO nanostructures (RGO/TiO2/ZnO) are growth by hydrothermal method and characterized by SEM, XPS, XRD, and UV-vis analyses. XRD analysis confirmed the formation of wurtzite ZnO and anatase TiO2 over the tandem nanostructure. The UV-vis spectrum indicated that the hybrid catalyst has the lowest band gap energy (E-g = 2.5 eV). Photocatalytic degradation of the catalysts towards estrogen (bisphenol-A) and pharmaceuticals (ibuprofen, flurbiprofen) was investigated under UV and visible light irradiation. The heterojunction RGO/TiO2/ZnO catalyst exhibited greater photocatalytic activity than bifunctional RGO/TiO2 and TiO2/ZnO. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Graphene oxide; TiO2; Photocatalytic degradation; Pharmaceutical; Estrogen; VISIBLE-LIGHT IRRADIATION; SENSITIZED SOLAR-CELLS; CARBON-FIBERS; METHYLENE-BLUE; DEGRADATION; COMPOSITE; NANOCOMPOSITES; ZNO; MECHANISM; WATER; Chemistry; Engineering